Accountability of Cash-Intensive on Village Funds (Case study in Kendal Village, Sekaran District, Lamongan Regency) - Dewi Kusmaya Sari; Ikhsan Budi Riharjo; Maswar Patuh Priyadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Accountability is an essential issue in scientific studies and practice in the field of public administration. Accountability in managing village funds has become a demand for the village government, as Law Number 6 of 2014 has been implemented concerning villages. Problems arise when the accountability of village funds’ labor- insentive cash is related to the new regulation. This policy requires village funds to be used for cash labor following SKB 4: the minimum wage must reach 30% of the total development sector sourced from the Village Fund. Therefore, this study aimed to describe and analyze cash accountability for labor in village funds (a case study in Kendal Village, Sekaran District, Lamongan Regency). Qualitative interpretive research was applied with interviews, observation, and documentation from official government documents. Furthermore, this study showed that the village fund accountability in Kendal Village, Sekaran District, Lamongan Regency has gradually implemented participation and transparency principles. The fund had met the wage requirements following SKB 4. The village had to reach 30% of the total development of the fund. Its implementation was carried out in a self-managed wanner involving workers from the poor, unemployed, and families with malnutrition, as evidenced by the ID card of Kendal villagers. Eventhough they experience obstacles in determining yhe poor’s criteria, the budget activity implementer (PKA) tries to apply accountability in the implementation of development based on the cash-insentive principle.